Influence of NUE genotypes on yield and nutrient use efficiency (NUE) parameters in the selection of K use efficient cassava genotypes - K. Susan John; M.N. Sheela (JOURNAL OF ROOT CROPS, 2025)
Abstract It is known that chemical fertilizers are one of the expensive inputs used by farmers to achieve desired crop yields along with improvement in soil fertility. But the recovery of applied inorganic fertilizers or the use efficiency of nutrients by plants is low in many soils due to various reasons and hence there exists a need to increase the nutrient use efficiency (NUE). Among the primary nutrients, K is considered as the ‘key nutrient’ for tuber crops due to its effect both on tuber yield and tuber quality. Hence, at ICAR- CTCRI, experiments were initiated since 2008 to screen K use efficient genotypes in cassava to reduce the use of chemical K fertilizers which in turn are fully imported. In this respect, detailed experiments for three seasons were conducted with six genotypes viz., Aniyoor, W-19, 7 Sahya-3, 6-6, CR 43-8 and 7III E3-5 selected from the preliminary screening of 83 elite genotypes at four levels of K viz., (0, 50, 100, 150 kg K2O ha-1) in a split plot design. This paper describes the independent effect of genotypes, years and interaction effect of genotypes over years on tuber yield and nutrient use efficiency parameters which in turn was used in the selection of most K efficient genotypes. The data generated on these parameters for the three years was statistically analysed using Genstat and seen significant independent effect of genotypes on tuber yield during first and third years, K uptake ratio (KUR) during the second and third years and percent K utilization for biomass (% KUB) during the third year. Pooled effect of genot over years was significant for tuber yield, utilization efficiency (UE), harvest index (HI), % K utilization for tuber (% KUT), K efficiency ratio (KER), K harvest index (KHI), K uptake ratio (KUR) and % K utilization for biomass (% KUB). Years imparted significant effect in the case of agro physiological efficiency (APE) and % KUB during the three years. The overall effect of years was significant for agronomic efficiency (AE), APE, KUR % KUB. The interaction effect of genotypes and years of experimentation was significant for tuber yield, KER, KUR and % KUB. Based on the studied parameters, Aniyoor and 7 III E3-5 was selected as K efficient.